2019
DOI: 10.1039/c8np00063h
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and biochemical characterisation of cyanotoxin biosynthesis pathways

Abstract: This review discusses cyanotoxin biosynthetic pathways and highlights the heterologous expression and biochemical studies used to characterise them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 230 publications
0
13
0
1
Order By: Relevance
“…Chemical and spectral data show that the lyngbyatoxin molecule is comprised of an indolactam ring, with an attached linalyl side group at C-7 (Figure 2E) [83]. So far, seven natural lyngbyatoxin analogues have been identified, namely lyngbyatoxin A-C, 12- epi -lyngbyatoxin A, 2-oxo-3( R )-hydroxy-lyngbyatoxin A, 2-oxo-3( R )-hydroxy- 13-N-desmethyllyngbyatoxin A and 2,3-seco-2,3-dioxolyngbyatoxin A [32,34,35]. Lyngbyatoxins are highly inflammatory and vesicatory substances derived from marine cyanobacteria [84].…”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical and spectral data show that the lyngbyatoxin molecule is comprised of an indolactam ring, with an attached linalyl side group at C-7 (Figure 2E) [83]. So far, seven natural lyngbyatoxin analogues have been identified, namely lyngbyatoxin A-C, 12- epi -lyngbyatoxin A, 2-oxo-3( R )-hydroxy-lyngbyatoxin A, 2-oxo-3( R )-hydroxy- 13-N-desmethyllyngbyatoxin A and 2,3-seco-2,3-dioxolyngbyatoxin A [32,34,35]. Lyngbyatoxins are highly inflammatory and vesicatory substances derived from marine cyanobacteria [84].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Lyngbyatoxins were first isolated from the lipid extract of a Hawaiian shallow-water variety of Lyngbya majuscula in 1979 [83]. Lyngbyatoxins have thus far been detected in the blooms of Lyngbya , Oscillatoria and Schizothrix [32,33]. A recent study found that it was also present in the Campania coast of southern Italy [87] (Table 1).…”
Section: Structural Characterizationmentioning
confidence: 99%
“…It was demonstrated that it had superior properties compared to previous reports of inducible promoter systems in cyanobacteria (Kelly et al, 2018). The native promoter from M. aeruginosa PCC 7806(native producer) was replaced for the heterologous production of microcystin-LR and [D-Asp3] microcystin-LR from E. coli GB05-MtaA (Cullen et al, 2018). Similarly, the recombinant microcystin synthetases gene cluster from M. aeruginosa PCC 7806 was heterologously expressed in E. coli to yield significant titer of [d-Asp3] microcystin-LR and microcystin-LR.…”
Section: Heterologous Production Of Cyanobacterial Compoundsmentioning
confidence: 99%
“…Cyanotoxins are therefore an important group of chemical compounds, from the perspective of ecotoxicology, toxicology and environmental chemistry (Cullen et al, 2019). Cyanotoxins can be divided on the basis of two main criteria: their action mechanism in land vertebrates, especially mammals, in three principal classes (hepatotoxins, neurotoxins and dermatotoxins) (Woese, 1987) and their chemical structure, within which they may be classified as cyclic peptides, alkaloids or lipopolysaccharides (LPS) (Cohen & Gurevitz, 2006;Ferrão-Filho & Kozlowsky-Suzuki, 2011;Zanchett & Oliveira-Filho, 2013).…”
mentioning
confidence: 99%